PENGARUH DANA ALOKASI UMUM TERHADAP PENDAPATAN ASLI DAERAH DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING (Studi Pada Pemerintah Kabupaten/Kota Se-Sumbagsel Tahun 2008-2012) - Vanchris, Deo Rizki; Fadli, Fadli; Aisyah, Siti (UNIB Press, 2013)
This research aims is to determine whether there are the effect of General Allocation Fund for Local Own Source Revenue, the effect of General Allocation Fund for Capital Expenditure, the effect of Capital Expenditure for Local Own Source Revenue, and the effect of General Allocation Fund for Local Own Source Revenue through Capital Expenditure. The samples used in this research are local governments of Sumbagsel in period 2008-2012. The analysis instrument used to determine the influence between variables was tested using linear regression analysis and used to the path analysis with SPSS program version 16.00. The results of research show that the General Allocation Fund has a positive effect on Local Own Source Revenue, the General Allocation Fund has a positive effect on Capital Expenditure, the Capital Expenditure has a positive effect on Local Own Source Revenue, and the General Allocation Fund has no effect on the Local Own Source Revenue through Capital Expenditure.